Teaching Procedures in Speaking for Social Intercultural Communication during Covid-19 Pandemic - Sherly Citra Putri (JETS: Journal of English Teaching Strategies, 2022)
This research article discussed the procedures of teaching speaking class during pandemic. In this case, the speaking class was purposed for social intercultural communication or lately called speaking 3. It was designed for 3rd semester students in English Department, Faculty of Teacher Training and Education in Mayjen Sungkono University of Mojokerto. This article was aimed to explain descriptively the steps for various topics in speaking class, especially in speaking for social intercultural communication course.